KONTRIBUSI PAJAK HIBURAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA MALANG (STUDI KASUS DINAS PENDAPATAN DAERAH KOTA MALANG) - Supriadi, Dara Rizky (Jurnal Mahasiswa Perpajakan, 2015)
Malang which is known as a student city with all it’s inhabitants, have made the number of entertainment as an essential needs for their daily activity. Now, as time goes by, the variety of entertainment venues can be found in Malang City. The local government of Malang City can take advantage of the entertainment sector as one of the local genuine income in view that entertainment is one of the important elements for the daily activity of the citizens of Malang City. The increasing number of entertainment tax payers in the city of Malang then automatically entertainment tax revenues will also get increased, so that later on will affect the contribution of tax revenue in the entertainment sector's local genuine income of Malang. This type of research is descriptive research, using data for fiscal year 2011-2014. The results of this research is that entertainment tax contributions against tax areas in the local genuine income is still very lacking. The average entertainment tax contribution to the local tax of 1,75% while the local genuine income about 1,25%. The level of effectiveness of entertainment tax and local genuine income above 100%, this indicates that the government has been able to carry out the regional financial sector performance the local genuine income very effectively. The local government of Malang City has also done some efforts to improve the entertainment tax, so that it’s contribution to the local genuine income will be greater. Keywords: Entertainment Tax, Local Genuine Income, Contribution, Effectiveness.